L’anaphore conceptuelle au prisme de la « théorie des blocs sémantiques » - Kohei Kida (Discours)
In order to account for the process of interpreting a demonstrative noun phrase in “conceptual” anaphora, we propose to describe the lexical semantic structure for its noun head in the framework of the “theory of semantic blocks”. By means of examples from a literary corpus, we will focus especially on the anaphoric expression cette persistance (“this persistence”), after describing the verb persister (“to persist”).